URGENSI LEMBAGA PENDIDIKAN ANAK USIA DINI (PAUD) DALAM RANAH KAJIAN MANAJEMEN PENDIDIKAN ISLAM - Darnoto Darnoto (Universitas Islam Nahdlatul Ulama Jepara, 2016)
ABSTRACTDiscussion in this study is directed to the three main studies, namely early childhood education, the position of early childhood education in the filed of Islamic education management study, and learning process of early childhood in accordance with the principles of Islamic education. Those studies above are described as follows. Early childhood education is a coaching efforts aimed at children from birth up to the age of six years done through the provision of educational stimulus to help improving physical and spiritual development so that children have readiness in entering the next level of education. Then the position of early childhood education in the study of Islamic education management becomes very important. Beside because of the development of the brain about the maximum absorption of children by the various stimuli provided by the environment, it is also inspired from the success of various units of education upward of it about the professional management of Islamic educational institutions that have brought about the achievements of parents and society. This is what must be prepared by early childhood institutions. Meanwhile, considering that early childhood education presents the concept of learning while playing, in which it is in accordance with their characteristic in being active in exploring the environment, so the implant of Islamic teachings as early as possible should be able to be implanted in their playing while learning process. Thus, the development and perfection of the potential abilities of children, such as language skills, social, emotional, motor, spiritual and intellectual, would be more guided. Keywords: urgency, early childhood education, Islamic education management.